2009
DOI: 10.5352/jls.2009.19.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Human IL-27p28 Gene Polymorphisms are Associated with the Serum Total IgE Levels of Allergic Rhinitis Patients

Abstract: Interleukin 27 (IL-27) was discovered as a heterodimeric cytokine of the IL-12 family, and is composed of two subunits -Epstein-Barr virus induced gene 3 (EBI3) and p28. It acts as a versatile cytokine in the early regulation of Th1 initiation and in the negative regulation of the Th2 factor GATA binding protein 3 (GATA-3). This cytokine is mediated by the IL-27 receptor (WSX-1), which is highly expressed on CD4 + T lymphocytes and NK cells. We previously identified four polymorphisms in the human IL-27p28 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…16 On the other hand, in accordance with the findings of our study, Ji-In Yu et al found that the frequencies of alleles and genotypes of rs181206 and rs153109 SNPs in AR patients and healthy controls in a Korean population were not significantly different. 32 Therefore, the results of this study, consistent with our findings, indicate that IL-27p28 SNPs (rs181206 and rs153109) may not be associated with AR susceptibility in some populations.…”
Section: Discussionsupporting
confidence: 88%
“…16 On the other hand, in accordance with the findings of our study, Ji-In Yu et al found that the frequencies of alleles and genotypes of rs181206 and rs153109 SNPs in AR patients and healthy controls in a Korean population were not significantly different. 32 Therefore, the results of this study, consistent with our findings, indicate that IL-27p28 SNPs (rs181206 and rs153109) may not be associated with AR susceptibility in some populations.…”
Section: Discussionsupporting
confidence: 88%